Equity-Based Crowdfunding in The Scheme Of Share Offering as an Expansion of The Categorization of Capital Market Activities: Implications and Orientation - Tuhana (Faculty of Law, Universitas Pekalongan, 2025)
The development of equity-based crowdfunding has become an expansion of the categorization of the capital market by fintech companies, potentially offering applications that function to connect owners with start-ups or Small and Medium Enterprises (SMEs) that need a capital injection. Problems arise when various regulations in Indonesia do not specifically address equity-based crowdfunding. This research aims to analyze the legal implications of the suboptimal regulation of equity-based crowdfunding, particularly in legislation, and how the future regulatory orientation relates to equity-based crowdfunding. This research is a normative legal study that emphasizes a conceptual and legislative approach. The research findings emphasize that the regulation of equity-based crowdfunding in Indonesia related to the capital market still does not provide clear legal certainty. This activity has not yet been detailed in the law, resulting in legal uncertainty that can harm investors and entrepreneurs. The ongoing practices are not yet equipped with regulations on accountability, transparency, and adequate legal protection. This also hinders small and medium-sized enterprises' access to crowdfunding platforms that can expand networks and technology. Therefore, more comprehensive regulations are needed, including technical and procedural regulations, the establishment of an independent regulatory body, licensing regulations for platforms, and strict supervision to protect investors and entrepreneurs. With these measures, it is hoped that equity-based crowdfunding practices can develop safely and efficiently in Indonesia